G287 Child maltreatment fatalities: A study of English serious case reviews, 2011–14. (27th April 2016) - Sidebotham, P; Bailey, S; Brandon, M; Harrison, E; Retzer, A
Abstract : Aims: To describe the features of all child maltreatment fatalities resulting in a Serious Case Review (SCR) in England in relation to the type of maltreatment fatality. Methods: Preliminary data were obtained from the Department for Education (DfE) on all SCRs between April 2011 and December 2013. SCR overview reports were obtained and scrutinised for case characteristics. The deaths were categorised according to a previously developed framework. Case characteristics were compared between different categories of death using comparative statistics. Results: A total of 194 child maltreatment fatalities were notified to DfE, of these, SCRs were obtained on 126 (65%). In 5 cases the death was not related to maltreatment; 6 were perpetrated by persons outside the family; and 3 cases could not be classified. A total of 194 child maltreatment fatalities were notified to DfE, of these, SCRs were obtained on 126 (65%). In 5 cases the death was not related to maltreatment; 6 were perpetrated by persons outside the family; and 3 cases could not be classified. Of the 112 remaining cases, 59 were directly caused by maltreatment, and 53 were related to but not directly caused by maltreatment (Table – serious case reviews), including sudden unexpected deaths in infancy with concerns about parenting or other evidence of abuse, and suicides where there were indications of child maltreatment in the background history. The different categories of death differed in relation to key characteristics, including the age of the child, whether or not they were known to social care, the relationship of the suspected perpetrator to the child, and background parental factors including the presence of domestic violence, mental health problems, and drug or alcohol abuse. 55% SCRs commented that the child's death could not have been predicted or prevented. However, qualitative analysis of the overview reports identified potentially modifiable factors in a majority of cases examined. Conclusions: Preventing child maltreatment fatalities does not depend on being able to accurately predict risk of death, but rather to understand the many and varied contexts within which children may be at risk.